Supermarket and Water Spider Concept for Improving Door Sub-Assembly Productivity - Barnas, Andreas; Pratama, Aditya T.; Awibowo, Setijo (Makara Journal of Technology, 2022)
This research is based on a case study at the door sub-assembly area of a German car manufacturer in Indonesia. The door sub-assembly area is responsible for assembling doors to be supplied to the specific station in assembly line that will assemble the finished doors to the car. The area had a problem in supplying the doors to the main assembly line on time. This means, the cycle time of door sub-assembly is higher than that of the assembly line. After observation, the factor that greatly contributes to the high cycle time can be identified, which is motion waste. Therefore, a unique approach is offered to overcome the situation, which involves re-designing work system and work area. The approach is to implement new working system by adopting lean tool water spider to significantly reduce motion waste. In the end, the initial and after condition will be contrasted to see the improvement made by this research. The results of this study could give the company several benefits: improved working efficiency of workers, reduced cycle time in door assembly and reduced fatigue of workers.